Development of coffee milk drink in can - Tanganco, Thessaly Ong; Francisco, Ma. Leonora dL. (1999.)
This study was aimed to develop coffee milk drink in can. It involves the formulation of the coffee milk drink, thermal processing and consumer acceptability of the final product. A preliminary study was conducted to choose between coffee milk samples made from coffee Liberica or "Kapeng Barako" and coffee blend of Arabica, Robusta and Excelsa. Results of data analysis did not show differences in the samples during the sensory evaluation. Based on the costing, the coffee blend was chosen. The formulation of coffee milk drink involved sensory evaluation for the determination of blends of coffee beans, type of milk and the milk levels. A blend of 50% Arabica, 30% Robusta and 20% Excelsa coffee grinds was chosen based on costing, since no differences were also detected in the data analysis. From the sensory evaluation, it was found that evaporated milk was preferred by the panelists in the amount of 25% in the coffee milk drink. The thermal processing of coffee milk at 250°F for 20 minutes resulted to an average F value of 22.14 minutes. This value exceeded the theoretical F value, which was 7.5 minutes. Verification of the process by physico-chemical tests, can examination and microbiological examinations indicated adequacy of the thermal process.Sensory evaluation for the consumer acceptability of the final product showed favorable responses. The coffee milk drink was described to be moderate brown with distinct aroma, moderate sweetness, right flavor and bitterness. Majority of the panelists stated that they like the product very much and would drink it very often.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coffee; Beverages